The Impact of the Implementation of the Tai Type Cooperative Learning Model on Mathematics Learning Outcomes at SMKN 2 Bukit Batu Flight - Farid Al Rashid; Riki Mukhaiyar; M Giatman; Dedy Irfan (JETL (Journal of Education, Teaching and Learning), 2025)
The low learning outcomes of mathematics at the Vocational High School (SMK) level is still a crucial problem in the world of education, especially in the context of conventional learning that does not involve optimal student activity. This study aims to analyze the influence of the Team Assisted Individualization (TAI) type cooperative learning model on the mathematics learning outcomes of class X students at SMKN 2 Aviation Bukit Batu. The approach used is a quantitative approach with a quasi experimental design method, using a Nonequivalent Control Group Design design. The study involved two classes of 30 students each, which were divided into an experimental group and a control group. The experimental group received a learning treatment using the TAI model for 12 meetings, while the control group followed conventional learning. The results showed that the average post-test score of the experimental group was 82.7, higher than the control group which only reached 72.5. The increase in scores from pre-test to post-test in the experimental group reached 20.3 points, while in the control group it was only 10.8 points. In addition, the level of learning completeness of students in the experimental group reached 90%, while in the control group it was only 60%. These findings show that the TAI learning model has a positive and significant influence on improving students' mathematics learning outcomes. The conclusion of this study is that the implementation of the TAI type cooperative learning model is effective in improving the mathematics learning outcomes of vocational school students, both in terms of increasing the average score and the percentage of learning completeness